Subwavelength metamaterial for communications and sensing - Wanguemert-Pérez, Juan Gonzalo; Sánchez-Postigo, Alejandro; Hadij-El-Houati, Abdelfettah; Pereira-Martín, Daniel; Luque-González, José Manuel; Leuermann, Jonas; Ortega-Moñux, Alejandro; Halir, Robert; Molina-Fernández, Íñigo; Cheben, Pavel; Xu, Dan-Xia; Schmid, Jens H.; et al. (My University, 2018)
Silicon photonics is considered a breakthrough technology with strong impact in areas as diverse as data center interconnection, high performance computing, the deployment of 5G future communication systems or lab-on-a-chip sensors. The emergence of sub-wavelength grating waveguides (SWG) has been fundamental to achieve advanced devices with unprecedented performance in integrated optics. In this talk we will focus on our recent progress in designing sub-wavelength engineered devices like ultra-broadband mode (de)multiplexers and converters [1], ultra-narrowband Bragg filters [2], sensing waveguides with enhanced sensitivity [3], or suspended silicon mid-infrared waveguides capable of covering the full transparency window of silicon [4], among other. This work was supported by the Ministerio de Economía y Competitividad, Programa Estatal de Investigación, Desarrollo e Innovación Orientada a los Retos de la Sociedad (Proyecto TEC2016-80718-R), and the Universidad de Málaga (Campus de Excelencia Internacional Andalucía Tech).
Keywords: Fotónica; Subwavelength grating waveguides; Photonic integrated circuits